An examination of short-run performance of IPOs using Extreme Bounds Analysis - Zubair Mumtaz, Muhammad; Smith, Zachary A.; Maqsood Ahmed, Ather (Estudios de Economía, 2016)
This paper estimates the short-run performance of IPOs issued on the Karachi Stock Exchange in Pakistan. The present study extends the existing literature concentrating on the degree of underpricing over a 3-month period lasting from the listing date to the 3-month anniversary showing significant evidence of IPO underpricing. The analyses support the investors' sentiment and underwriters' prestige hypothesis but not ex-ante uncertainty. The EBA technique has been used to examine fifteen explanatory variables of IPO underpricing. The study finds that the aftermarket risk level of the IPO, the oversubscription ratio, the offer price, the return on assets, post issue promoters' holding and size of the firm are six robust determinants of IPO underpricing.